A Novel Mechanism of Ataxia Telangiectasia Mutated Mediated Regulation of Chromatin Remodeling in Hypoxic Conditions - Likhatcheva, Maria; Gieling, Roben G.; Brown, James A. L.; Demonacos, Constantinos; Williams, Kaye J. (Frontiers in Cell and Developmental Biology, 2021)
The effects of genotoxic stress can be mediated by activation of the Ataxia Telangiectasia Mutated (ATM) kinase, under both DNA damage-dependent (including ionizing radiation), and independent (including hypoxic stress) conditions. ATM activation is complex, and primarily mediated by the lysine acetyltransferase Tip60. Epigenetic changes can regulate this Tip60-dependent activation of ATM, requiring the interaction of Tip60 with tri-methylated histone 3 lysine 9 (H3K9me3). Under hypoxic stress, the role of Tip60 in DNA damage-independent ATM activation is unknown. However, epigenetic changes dependent on the methyltransferase Suv39H1, which generates H3K9me3, have been implicated. Our results demonstrate severe hypoxic stress (0.1% oxygen) caused ATM auto-phosphorylation and activation (pS1981), H3K9me3, and elevated both Suv39H1 and Tip60 protein levels in FTC133 and HCT116 cell lines. Exploring the mechanism of ATM activation under these hypoxic conditions, siRNA-mediated Suv39H1 depletion prevented H3K9me3 induction, and Tip60 inhibition (by TH1834) blocked ATM auto-phosphorylation. While MDM2 (Mouse double minute 2) can target Suv39H1 for degradation, it can be blocked by sirtuin-1 (Sirt1). Under severe hypoxia MDM2 protein levels were unchanged, and Sirt1 levels depleted. SiRNA-mediated depletion of MDM2 revealed MDM2 dependent regulation of Suv39H1 protein stability under these conditions. We describe a novel molecular circuit regulating the heterochromatic state (H3K9me3 positive) under severe hypoxic conditions, showing that severe hypoxia-induced ATM activation maintains H3K9me3 levels by downregulating MDM2 and preventing MDM2-mediated degradation of Suv39H1. This novel mechanism is a potential anti-cancer therapeutic opportunity, which if exploited could target the hypoxic tumour cells known to drive both tumour progression and treatment resistance.